Glycoprotein Hormone Receptor Knockdown Leads to Reduced Reproductive Success in Male Aedes aegypti - Rocco, David A.; Garcia, Ana S. G.; Scudeler, Elton L.; dos Santos, Daniela C.; Nóbrega, Rafael H.; Paluzzi, Jean-Paul V. (Frontiers in Physiology, 2019)
Glycoprotein hormone receptors mediate a diverse range of physiological functions in vertebrate and invertebrate organisms. The heterodimeric glycoprotein hormone GPA2/GPB5 and its receptor LGR1, constitute a recently-discovered invertebrate neuroendocrine signaling system that remains to be functionally characterized. We previously reported that LGR1 is expressed in the testes of adult Aedes aegypti mosquitoes, where its immunoreactivity is particularly regionalized. Here, we show that LGR1 immunoreactivity is associated with the centriole adjunct of spermatids and is observed transiently during spermatogenesis in mosquitoes, where it may act to mediate the regulation of flagellar development. RNA interference to downregulate LGR1 expression was accomplished by feeding mosquito larvae with bacteria that produced LGR1-specific dsRNA, which led to defects in spermatozoa, characterized with shortened flagella. LGR1 knockdown mosquitoes also retained ~60% less spermatozoa in reproductive organs and demonstrated reduced fertility compared to controls. To date, the endocrine regulation of spermatogenesis in mosquitoes remains an understudied research area. The distribution of LGR1 and detrimental effects of its knockdown on spermatogenesis in A. aegypti indicates that this heterodimeric glycoprotein hormone signalling system contributes significantly to the regulation of male reproductive biology in this important disease-vector.